The Implementation of Higher Order Thinking Skills (HOTS) in English Language Teaching: A Case of Indonesian Senior High School EFL Teachers - Ramadan Fitriani; Ifan Iskandar; Muchlas Suseno (Didaktika: Jurnal Kependidikan, 2023)
This research explored Indonesian EFL teachers' perceptions of implementing higher-order thinking Skills (HOTS) in English language classrooms. Specifically, it attempted to explore (1) teachers' understanding of HOTS, (2) teachers' perceptions of the implementation of HOTS in their EFL classrooms, and (3) teachers' perceived obstacles in the implementation of HOTS. The research employed a qualitative approach with a case study design. Five English language teachers at a senior high school in Serang Banten Province, Indonesia, participated in this research. The data were collected using semi-structured interviews and were analyzed following Miles and Huberman's (1994) qualitative data analysis procedures. The results revealed that all participants had a good understanding of the concept of HOTS, in which the definitions of HOTS given by all the participants were related to the sub-skills of Bloom's Taxonomy. All the participants also claimed they had implemented HOTS in English language teaching and learning. However, the implementation has yet to be effective due to some obstacles, which include students' low English proficiency, teachers' lack of competencies, and limited supporting facilities such as internet access, learning media, and learning sources.